Membedah Hermeneutika Perspektif Ilmuan Muslim Modern: Korelasinya dalam Studi Ilmu Hadits - Mohammad Jailani; Jannatul Husna; Nur Kholis (AL QUDS : Jurnal Studi Alquran dan Hadis, 2022)
Dissecting Hermeneutics from the Perspective of Modern Muslim Scientists: Its Correlation in the Study of Hadith SciencesThe development of Islamic studies in modern times affects information technology and the science of hadith is growing so rapidly. One of them is evidenced by the research base in 2021-2022 in Google Scholar, Science Direct, many academics have responded. The purpose of this study is to analyze the hermeneutical method of hadith from the point of view of modern Muslim scientists. This study uses the Research Library method. The data was obtained by capturing relevant journal articles through Google Scholar and Scientific Direct. Data analysts follow Miles and Huberman with the knife of theoretical triangulation analysis and documentation grids. The results of this study interpret those hermeneutics in the study of hadith as very broad and very dense in scope. Not only in the scope of the Qur'an, but also the hadith, it is also very religious, even the principles in hadith hermeneutics also exist. Muslim scientists who specialize in hermeneutics in the study of hadith include Fazlur Rahman with his Double Movement theory, Nasr Abu Hamid Zaid with his semantic hermeneutics in the study of jihad hadith, Muhammad Musthofa A'Zani with his criticism of the authenticity of his hadith, Hans Georg Gadamer with his philosophical hermeneutics, and Paul Ricoeur with his text Hermeneutics on the scope of hadith about mahram. Thus, the contribution or implications of this research focus on analyzing the hermeneutics developed by modern Muslim scientists. Hermeneutics is closely correlated with the study of hadith science today